Predictors of heart failure at 3-month follow-up in patients undergoing pharmacoinvasive percutaneous coronary intervention for anterior wall STEMI: A cross-sectional study. - Dr. Ramesh R S; Velappan, Praveen; Bijesh S (Student’s Journal of Health Research Africa, 2025)
Background Anterior wall ST-elevation myocardial infarction (STEMI) often leads to left ventricular (LV) dysfunction and clinical heart failure despite timely reperfusion. The pharmacoinvasive percutaneous coronary intervention (PCI) strategy, involving thrombolysis followed by planned PCI, is frequently used in regions where immediate primary PCI is not feasible. Identifying early predictors of heart failure after such interventions can improve risk stratification and follow-up strategies. Objectives To identify the baseline angiographic and clinical indicators of heart failure at the 3-month mark in patients who received PCI and thrombolysis for anterior wall STEMI. Methods 480 individuals who received PCI and thrombolysis for anterior wall STEMI within 24 hours were included in this research. Age, gender, Killip class, cardiovascular risk factors, time to PCI (3–10, 10–17, and 17–24 hours), Baseline data included left ventricular ejection fraction (LVEF) at discharge and TIMI flow prior to and following PCI. At three months, heart failure was defined as echocardiographic LV dysfunction (LVEF <40%) and the presence of NYHA class II–IV symptoms. Independent predictors were found using multivariate logistic regression. Results Mean age was 57.3 ± 11.2 years; 82% were male. Sixty-eight patients (14.2%) developed HF at 3 months. HF was more common among those with Killip class ≥II (29.5% vs. 9.8%, p<0.001), delayed PCI (>17 hours) (20% vs. 10.3%, p=0.01), and lower baseline LVEF (40.1% vs. 46.7%, p<0.001). Independent predictors were baseline LVEF <40% (aOR 2.78, 95% CI 1.63–4.72), Killip class ≥II (aOR 2.15, 95% CI 1.24–3.71), and PCI >17 hours (aOR 1.96, 95% CI 1.08–3.57). Conclusion Low baseline LVEF, elevated Killip class, and PCI delay independently predict HF at 3 months following pharmacoinvasive PCI for anterior STEMI. Recommendation Early risk identification, minimizing PCI delays, and aggressive heart failure prevention strategies